Estandarización de una técnica de reacción en cadena de polimerasa (PCR) para detección de Herpesvirus bovino-1 en semen (1996)
ABSTRACT: BHV-1 can be found in semen from seropositive animals, but the frequency of excretion and the impact of this route for the dissemination of the infection have not been established. In order to improve the sensibility of detection of the virus in semen, we attempted to standardize a PCR. As previously reported by others investigators we found that semen contains PCR inhibitory factors that makes it necessary to dilute the samples up to 1:6000 or more to obtain DNA amplification. With the purpose of increasing the sensibility of the assay, the amplified PCR product was detected by southern blot with an oligonucleotide probe internal to the amplified fragment, Preliminary assays showed a 100 fold increase in the sensibility with this strategy. Despite the high dilution of the semen sample, we could detected the virus in samples collected from bulls from herds with symptoms compatible with Infectious Bovine Rinotracheitis (IBR). This PCR could be used in quality control of specimens used in programs of artificial insemination and embryo transfer. In addition, it could be of used for the determination of the biological implications of this route of virological excretion.